Biosynthesis of chartreusin and in vitro elucidation of unknown dehydration reactions - Rauhanen, Katariina (My University, 2025)
Anthracyclines are aromatic polyketide antibiotics produced in bacteria genus Streptomyces. Anthracyclines possess many medically interesting bioactivities, and some are among the most effective cancer drugs. One important anthracycline, chartreusin, has been researched for its antibacterial activity, and many steps of its biosynthetic pathway have been elucidated. Chartreusin is structurally very similar to a potent cancer drug elsamicin A. Detailed knowledge of the biosynthetic pathway of chartreusin is essential for production of new compounds by genetic engineering and synthetic biology to gain improved drugs. Anthracyclines are biosynthesized by type II polyketide synthases (PKSs), which first form a highly reactive polyketide carbon chain. Stable polycyclic anthracycline intermediates are made by accessory PKSs for example aromatases and cyclases. Tailoring enzymes, for example oxidases and glycosylases, form the final bioactive products. Tailoring steps are rather complex and make anthracyclines a chemically diverse group. The aim of this study was to find out which tailoring enzymes in the chartreusin pathway catalyze the conversion from auramycinone to resomycin C, a process where two dehydration reactions occur. The products from enzymatic assays were assessed with UPLC, LC-MS and NMR. The results suggest a two-step conversion from auramycinone to resomycin C. Fist an NADPH dependent reductase ChaX and cyclase-like ChaU catalyze one dehydration using auramycinone as a substrate. The second dehydration is catalyzed by a cyclase-like ChaJ or alternatively by ChaX/ChaU pair. An interesting aspect with these results is the novel dehydratase reactions catalyzed by the cyclase-like proteins. Previously only two different functions have been associated with the protein family: hydroxylation and aldol condensation. Proteins in the same family catalysing very different chemical reactions is probably a result of mutations in catalytic amino acids. For this reason, crystallization experiments have been initiated to solve the crystal structures of ChaU and ChaJ and to understand how a total switch in their chemistry has happened.
Keywords: anthracyclines, Streptomyces, antibiotic biosynthesis, chartreusin